The genetics of abdominal aortic aneurysm - Harrison, Seamus (Henry Stewart Talks, 2013)
Epidemiology of AAA, AAA risk factors, AAA vs. Atherosclerosis, Pathology of AAA, AAA management, AAA natural history, Screening for AAA, Surgical repair of AAA, Genetics of AAA, Monogenic aortic diseases, Familial studies, Meta-analysis of candidate genes, Chromosome 9p21 & 9q33 and risk of AAA, Aneurysm consortium GWAS AAA results, Regional association with CHD, Future directions